A quadtree-polygon-based scaled boundary finite element method for crack propagation modeling in functionally graded materials. (April 2018) - Chen, X.; Luo, T.; Ooi, E.T.; Ooi, E.H.; Song, C.
Highlights: A hybrid-quadtree-polygon method to model fracture in functionally graded materials. Improved computational efficiency through pre-calculation of generic quadtree cells. Accurate and simple approach for computation of fracture parameters in functionally graded materials. A quadtree-polygon-based remeshing algorithm for efficient modelling of crack propagation. Numerical benchmarks demonstrate the efficiency and accuracy of the developed approach. Abstract: This paper presents a method to improve the computational efficiency of the scaled boundary finite element formulation for functionally graded materials. Both isotropic and orthotropic functionally graded materials are considered. This is achieved using a combination of quadtree and polygon meshes. This hybrid meshing approach is particularly suitable to be used with the SBFEM for functionally graded materials because of the significant amount of calculations required to compute the stiffness matrices of the polygons/cells in the mesh. When a quadtree structure is adopted, most of the variables required for the numerical simulation can be pre-computed and stored in the memory, retrieved and scaled as required during the computations, leading to an efficient method for crack propagation modeling. The scaled boundary finite element formulation enables accurate computation of the stress intensity factors directly from the stress solutions without any special post-processing techniques or local mesh refinement in the vicinity of the crack tip. Numerical benchmarks demonstrate the efficiency of the proposed method as opposed to using a purely polygon-mesh based approach.